Some Elements of the Expansion Mechanism in the World Economy - BORBASOVA, Ziada; OSSIK, Yuri; TOLYSBAYEV, Baurzhan; ULAKOV, Sairan; MARAT, Syrlybayev (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
In this paper considered the simulation as a tool for economic expansion in modern conditions of socio-economic development. Discussed the relationship between expansion and competition. Given evidence of much larger economic success in the global market firms, practicing mainly in simulation activities, compared to innovative firms. As a successful business simulation is an example of Chinese firms. Also shown that successful firms combine the innovative and imitative activities. Given that the first companies on the market of goods and services is much more than the second, it is proposed to develop a simulation direction in theoretical and applied economic science at the crossroads of theory and practice of law.